(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): In the era of dynamic transition towards sustainable practices in procurement functions, a notable gap emerges in understanding which sustainability criteria organizations use in supplier selection. This study aims to bridge this gap by posing questions: RQ1: "Which sustainability-related criteria should be integrated into the supplier selection process?" and RQ2: "What is the relationship between research methodologies and types of contributions in the literature examining sustainability issues?" Purpose: The primary aim of this research is to analyse and understand the integration of sustainable practices into supplier selection processes, with a focus on identifying key sustainability criteria used by organizations in evaluating potential suppliers, and how these criteria influence the decision-making process. Method: To achieve the research objectives, a systematic literature review was conducted using the PRISMA method. This approach enabled a comprehensive, structured, and unbiased analysis of existing studies, ensuring the validity and reliability of the research. Results: We addressed both research questions and confirmed the thesis. The study revealed a diversity of sustainability criteria considered by companies, covering economic, environmental, and social dimensions. Analysis of 21 publications demonstrated an increasing trend in the inclusion of sustainability criteria in supplier evaluations, highlighting a multidimensional approach to sustainability. Organization: The findings of the study have a significant impact on procurement managers and practitioners, as they present a framework for the strategic integration of sustainability criteria into supplier selection, thereby improving organizational practices and contributing to the strategic value of procurement functions. Society: The study emphasizes the broader impact on society and the environment, advocating for a shift towards more responsible and sustainable procurement practices. It highlights the role of sustainable supplier selection in promoting environmental responsibility, social accountability, and contributing to global sustainability goals. Originality: The research contributes original insights into the integration of sustainability criteria into supplier selection, offering a new perspective on procurement practices. It provides a novel approach to using the PRISMA method for analysing sustainability in procurement, enhancing the methodological rigor and applicability of the research. Limitations / further research: While the study brings significant insights, it acknowledges limitations such as the restriction to recent publications and reliance on specific databases. It suggests directions for further research, including exploring diverse methodologies, conducting comparative and longitudinal studies, and examining the impact of sustainable practices on consumer behaviour.